Degrading Endocrine Disrupting Chemicals fromWastewater by TiO2 Photocatalysis: A Review - Sin, Jin Chung; Lam, Sze Mun; Mohamed, Abdul Rahman; Lee, Keat Teong (Hindawi Publishing Corporation, 2012)
Widespread concerns continue to be raised about the impacts of exposure to chemical compounds with endocrine disrupting activities. To date, the percolation of endocrine disrupting chemical (EDC) effluent into the aquatic system remains an intricate challenge abroad the nations. With the innovation of advanced oxidation processes (AOPs), there has been a consistent growing interest in this research field. Hence, the aim of this paper is to focus one such method within the AOPs, namely, heterogeneous photocatalysis and how it is used on the abatement of EDCs, phthalates, bisphenol A and chlorophenols in particular, using TiO2-based catalysts. Degradation mechanisms, pathways, and intermediate products of various EDCs for TiO2 photocatalysis are described in detail. The effect of key operational parameters on TiO2 photocatalytic degradation of various EDCs is then specifically covered. Finally, the future prospects together with the challenges for the TiO2 photocatalysis on EDCs degradation are summarized and discussed.